Associations Between Medicare Part D and Out-of-Pocket Spending, HIV Viral Load, Adherence, and ADAP Use in Dual Eligibles With HIV. Issue 1 (January 2018) - Belenky, Nadya; Pence, Brian W.; Cole, Stephen R.; Dusetzina, Stacie B.; Edmonds, Andrew; Oberlander, Jonathan; Plankey, Michael W.; Adedimeji, Adebola; Wilson, Tracey E.; Cohen, Jennifer; Cohen, Mardge H.; Milam, Joel E.; et al.
Abstract : Background: The implementation of Medicare part D on January 1, 2006 required all adults who were dually enrolled in Medicaid and Medicare (dual eligibles) to transition prescription drug coverage from Medicaid to Medicare part D. Changes in payment systems and utilization management along with the loss of Medicaid protections had the potential to disrupt medication access, with uncertain consequences for dual eligibles with human immunodeficiency virus (HIV) who rely on consistent prescription coverage to suppress their HIV viral load (VL). Objective: To estimate the effect of Medicare part D on self-reported out-of-pocket prescription drug spending, AIDS Drug Assistance Program (ADAP) use, antiretroviral adherence, and HIV VL suppression among dual eligibles with HIV. Methods: Using 2003–2008 data from the Women's Interagency HIV Study, we created a propensity score–matched cohort and used a difference-in-differences approach to compare dual eligibles' outcomes pre-Medicare and post-Medicare part D to those enrolled in Medicaid alone. Results: Transition to Medicare part D was associated with a sharp increase in the proportion of dual eligibles with self-reported out-of-pocket prescription drug costs, followed by an increase in ADAP use. Despite the increase in out-of-pocket costs, both adherence and HIV VL suppression remained stable. Conclusions: Medicare part D was associated with increased out-of-pocket spending, although the increased spending did not seem to compromise antiretroviral therapy adherence or HIV VL suppression. It is possible that increased ADAP use mitigated the increase in out-of-pocket spending, suggesting successful coordination between Medicare part D and ADAP as well as the vital role of ADAP during insurance transitions.